2011
DOI: 10.1038/ejcn.2011.38
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient recommendation stakeholders' beliefs on dietary guidelines: a qualitative study across six European countries/regions

Abstract: A range of stakeholders have been involved in the development and implementation of dietary guidelines (DG) across Europe. Seventy-seven semi-structured qualitative interviews explored stakeholders' beliefs of DG in six European countries/regions. A main theme, variation in the interpretation of the term dietary guideline, was identified using thematic analysis. Descriptions of DG varied across stakeholder groups and countries. Reference was made to both food-based and nutrient-based guidelines, including the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The term ‘dietary guideline’ was believed to be the most understandable and translatable term across stakeholders and countries and was initially used in section 1 of the interview schedule. Previously published results from this data set reported variation in the interviewee-led interpretation of the term ‘dietary guideline’ ( 26 ) . Thus, the reader should be aware that ‘dietary guideline’ has referred to both nutrient- and food-based recommendations throughout the present paper.…”
Section: Methodsmentioning
confidence: 70%
See 1 more Smart Citation
“…The term ‘dietary guideline’ was believed to be the most understandable and translatable term across stakeholders and countries and was initially used in section 1 of the interview schedule. Previously published results from this data set reported variation in the interviewee-led interpretation of the term ‘dietary guideline’ ( 26 ) . Thus, the reader should be aware that ‘dietary guideline’ has referred to both nutrient- and food-based recommendations throughout the present paper.…”
Section: Methodsmentioning
confidence: 70%
“…It is unclear the degree these past negative or positive experiences of consumer involvement may have influenced any assumptions about consumers and consumer involvement reported in the study. In addition, the confusion surrounding the terminology in this area ( 26 , 40 ) has led to the present study interviewing those responsible for and collecting results referring to a variety of nutrient- and food-based guidelines (Dietary Reference Values, nutrient goals, Food-Based Dietary Guidelines).…”
Section: Discussionmentioning
confidence: 99%
“…Differences persist in the terminology used by national and international bodies tasked with setting DRV. A qualitative analysis of stakeholder beliefs in dietary guidelines across Europe identified a need for greater clarity about the terminology used (61) .…”
Section: European Food Safety Authoritymentioning
confidence: 99%
“…EURRECA has been aware of the relevance of its work to the NRSBs from its very beginning, which has resulted in research into the organisation of NRSBs in Europe [8], populations at risk of low micronutrient intake [9] and potential policy options, with case studies that involved some of the NRSBs [10]. To further facilitate the derivation of DRVs, EURRECA has highlighted the topics that require additional research and has identified which nutrients/health outcomes should be prioritised for research by age or population group [11].…”
Section: Next Stepsmentioning
confidence: 99%